Selecting Remote Measurement Technologies to Optimize Assessment of Function in Early Alzheimer's Disease: A Case Study - Owens, Andrew P.; Hinds, Chris; Manyakov, Nikolay V.; Stavropoulos, Thanos G.; Lavelle, Grace; Gove, Dianne; Diaz-Ponce, Ana; Aarsland, Dag (Frontiers in Psychiatry, 2020)
Despite the importance of function in early Alzheimer’s disease (AD), current measures are outdated and insensitive. Moreover, COVID-19 has heighted the need for remote assessment in older people, who are at higher risk of being infection and are particularly advised to use social distancing measures, yet the importance of diagnosis and treatment of dementia remains unchanged. The emergence of remote measurement technologies (RMTs) allows for more precise and objective measures of function. However, RMT selection is a critical challenge. Therefore, this case study outlines the processes through which we identified relevant functional domains, engaged with stakeholder groups to understand participants’ perspectives and worked with technical experts to select relevant RMTs to examine function. After an extensive literature review to select functional domains relevant to AD biomarkers, quality of life, rate of disease progression and loss of independence, functional domains were ranked and grouped by the empirical evidence for each. For all functional domains, we amalgamated feedback from a patient advisory board. The results were prioritised into: highly relevant, relevant, neutral and less relevant. This prioritised list of functional domains was then passed onto a group of experts in the use of RMTs in clinical and epidemiological studies to complete the selection process, which consisted of: i) identifying relevant functional domains and RMTs; ii) synthesizing proposals into final RMT selection, and iii) verifying the quality of these decisions. Highly relevant functional domains were, ‘difficulties at work’, ‘spatial navigation and memory’, and ‘planning skills and memory required for task completion’. All functional domains were successfully allocated commercially available RMTs that make remote measurement of function feasible. This case study provides a set of prioritised functional domains sensitive to the early stages of AD and a set of RMTs capable of targeting them. RMTs have huge potential to transform the way we assess function in AD - monitoring for change and stability continuously within the home environment, rather than during infrequent clinic visits. Our decomposition of RMT and functional domain selection into identify, synthesize, and verify activities, provides a pragmatic structure with potential to be adapted for use in future RMT selection processes.